2002
DOI: 10.1029/2001jb000556
|View full text |Cite
|
Sign up to set email alerts
|

Sonic waveform attenuation in gas hydrate‐bearing sediments from the Mallik 2L‐38 research well, Mackenzie Delta, Canada

Abstract: [1] The Mallik 2L-38 research well was drilled to 1150 m under the Mackenzie Delta, Canada, and penetrated a subpermafrost interval where methane hydrate occupies up to 80% of the pore space. A suite of high-quality downhole logs was acquired to measure in situ the physical properties of these hydrate-bearing sediments. Similar to other hydrate deposits, resistivity and compressional and shear sonic velocity data increase with higher hydrate saturation owing to electrical insulation of the pore space and stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
131
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 41 publications
(97 reference statements)
20
131
5
Order By: Relevance
“…Because the presence of gas hydrates increases the velocities, the concentration of gas hydrates in sediments is usually estimated using seismic velocity models (Ecker et al, 1998;Lee and Collett, 2001;Gei and Carcione, 2003;Chand et al, 2004). The presence of gas hydrates in sediments has a pronounced effect on the amplitude and frequency characteristics of a seismic signal also (Guerin and Goldberg, 2002;Pratt et al, 2003;Chand and Minshull, 2004). Hydrates in sediments show contradicting amplitude characteristics in seismic sections such as amplitude blanking (Korenaga et al, 1997) and amplitude enhancements (Nouzé et al, 2004;Riedel et al, 2010;Yoo et al, 2013) at different geologic settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the presence of gas hydrates increases the velocities, the concentration of gas hydrates in sediments is usually estimated using seismic velocity models (Ecker et al, 1998;Lee and Collett, 2001;Gei and Carcione, 2003;Chand et al, 2004). The presence of gas hydrates in sediments has a pronounced effect on the amplitude and frequency characteristics of a seismic signal also (Guerin and Goldberg, 2002;Pratt et al, 2003;Chand and Minshull, 2004). Hydrates in sediments show contradicting amplitude characteristics in seismic sections such as amplitude blanking (Korenaga et al, 1997) and amplitude enhancements (Nouzé et al, 2004;Riedel et al, 2010;Yoo et al, 2013) at different geologic settings.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, mainly on surface seismic data (Matsushima, 2006;Rossi et al, 2007;Dewangan et al, 2014) indicated a decrease in attenuation. The increase (Guerin and Goldberg, 2002;Gei and Carcione, 2003;Chand and Minshull, 2004;Lee and Collett, 2006) and decrease (Sain and Singh, 2011;Dewangan et al, 2014) in attenuation have been explained by using different rockphysics models depending on the assumed microstructure of the hydrate and also sediment-hydrate mixtures. Chand and Minshull (2004) suggest that the amount of attenuation not only changes with hydrate saturation but also with the frequency of the seismic signal.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of downhole acoustic log data from both marine-and permafrost-associated gas hydrate accumulations have shown that the volume of gas hydrate in sediment can be estimated by measuring interval velocities (Guerin et al, 1999;Helgerud et al, 2000;Collett, 2000). Analysis of sonic logging waveforms has also shown that the presence of gas hydrate can generate significant energy loss in monopole and dipole waveforms (Guerin and Goldberg, 2002).…”
Section: Acoustic Transit Timementioning
confidence: 99%
“…Gas hydrates affect the rock properties, so the wave attenuation in hydrate-bearing sediments is a complex phenomenon. In Mackenzie Delta, Canada, Guerin and Goldberg [1], Guerin et al [2], and Pratt et al [3] obtained high value of wave attenuation in hydrate-bearing sediments by logging data and crosshole seismic tomography results, respectively. In Nankai Trough, central Japan, Matsushima [4] also proved that elastic wave showed strong attenuation in hydrate-bearing sediments by logging data, in Blake Ridge and in the Makran Accretionary Prism, Arabian Sea, Wood et al [5] and Sain and Singh [6] obtained week attenuation of seismic wave in hydrate-bearing sediments by using seismic data.…”
Section: Introductionmentioning
confidence: 99%